Effect of Galvanic Metallization, PVD Processes and Thermal Spraying on Fatigue Properties of Plain Structural Steels in the Ultra-High-Cycle Regime - Frantisek Novy; Rastislav Mintach; Otakar Bokuvka (Communications - Scientific letters of the University of Zilina, 2010)
This work presents information about the influence of Ni and ZnFe galvanic metallization on the fatigue properties of S235JRG2 steel and about the TiN physical vapour deposition and WC thermal spraying on the fatigue properties of S355J0 steel in the ultra-high-cycle region of loading (N 6106 – 1010 cycles) obtained at high-frequency fatigue testing (f 20 kHz, T 20 3 °C, R 1). Technical coatings are used in order to modify the properties of the surface that is being covered for protection against corrosion but also in order to increase the hardness and resistance to wear. The Ni coating produced by galvanic metallization favourably influences the corrosion resistance but it introduces tensile stresses into the surface layer which act negatively on fatigue properties. No evidence of improving fatigue lifetime was detected in the case of ZnFe, TiN and WC coatings. In all types of coating the fatigue cracks were initiated on the specimen surface e.g. on the coatings surfaces.